Supplemental Oxygen and Hyperoxia in Critically Ill Children. Issue 4 (July 2022) - Beal, Judy A.
Abstract : Supplemental oxygen is often administered to critically ill children in the pediatric intensive care unit and can result in hyperoxia. Our pediatric nursing expert, Dr. Beal, highlights a recently published systematic review and meta-analysis on the association of hyperoxia with outcomes in critically ill children. Data on hyperoxia in critically ill children are scant. Although the analysis had multiple limitations including lack of randomized clinical trials, small sample sizes, lack of statistical significance, lack of correction for severity of illness, study design heterogeneity, and the need to pool data, cautious use of oxygen for this patient population is warranted, and when given, the goal should be normoxia, rather than hyperoxia. Further study by pediatric nurse researchers would be helpful for this clinical question.